(3XdGd OehjIs (3MJi dG JbY aj GdaN (B: (3QhGjIs - (3YWjJh, ecGQjhSs; (3efJUQ, eQjes ((3GdbGgQIs (3GdafGQs, 2023)
(3gPg GdUaMGJ Sha JLYdce JZpqjQhf GJLGgce fMh GdTJGA hcBHJg(B.. (3aCfJe CeGe bGJd eJSdSd dG jYQa GdQMeI, hUfOhlb ZGelV, hefRd edYhf(B.. (3cdge jQJHWhf HTjmA hGMO(B.. (3SJOhQ aj CPgGfce LejY CfhGY GdGSFdI, hdf JUdhf Edi Cqj ELGHGmJ EdG eY NqW GdfgGjI(B. (3eG SJbQChfg SjLYdce dG JYQahf gd JJYGWahf eY GdbGJd Ce GdebJhd?(B!s
Keywords: (3GdbUU GdYQHjIs -- (3eUQs